Debating climate law - Mayer, Benoit; Zahar, Alexander (Cambridge : Cambridge University Press, 2021)
What role could or should the law play in dealing with the climate emergency? In this innovative volume, leading scholars explore fundamental debates at the frontier of climate change law scholarship. They address the key areas of scholarly disagreement about what climate change law is, the legal rules it consists of, and how these rules could be implemented in the real world. The first eleven topics are debated by teams of scholars expressing diametrically opposite points of view on each topic, in traditional debating style; the last seven chapters are presented as an individual author's own reflection on a topic that cannot readily be reduced to a binary debate. Each chapter is written in an accessible and thought-provoking way, emphasizing clear lines of argumentation. The debating-style format is designed to stimulate students to think critically and logically about the law and to fire up debate in and out of class.
Title from publisher's bibliographic system (viewed on 18 Jun 2021).
Keywords: Climatic changes -- Law and legislation